ABOUT INFLUENCE OF CONCRETE SLAB REINFORCEMENT ON PLATE RESISTANCE TO PUNCHING FORCE - A. I. Mordich; V. N. Belevich; D. I. Navoy; D. M. Mordich (Наука и техника)
The paper presents experimental research results and their analysis in respect of flat reinforced concrete slabs resting on point supports or soil in case of concentrated punching force. However the conducted researches have shown a number of incompatibilities accepted in computational model standards that appear in the form of critical parameters in the punching zone and configuration of computational (critical) sections in comparison with an actual pattern of slab crack formation and their collapse in the places of concentrated force application. Moreover, the computational methods do not take into account at all an influence of longitudinal reinforcement on both principal axis of the building frame or take it into account this phenomenon by empirical dependence indirectly. In view of the above-mentioned facts an accumulation of new experimental data is considered as an expedient process with the purpose to identify a physical pattern of flat reinforced concrete slabs operation under concentrated punching force. The paper makes it possible to revise a calculative methodology and, preserving a high reliability, it also permits to improve efficiency of a floor construction of the whole framework. It has been determined that longitudinal reinforcement of reinforced concrete slabs is actively involved in their work under concentrated punching force and exerts a prominent influence on their resistance to punching force. The paper presents a possible approach pertaining to evaluation of a longitudinal reinforcement influence on resistance of reinforced concrete slabs to punching force with due account of regulations of the appropriate standardized documents.